Hukum Jual Beli Followers di Media Sosial Instagram dalam Perspektif Perbandingan Mazhab - M. Kasim; Sirajuddin Sirajuddin; Tita Ratna Irmawati (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This study aims to analyze the laws of buying and selling followers on Instagram social media in the perspective of the four schools of thought and to conduct a comparative study of the opinions of the four schools of thought. The type of research used is library research, with a normative and philosophical approach. The results of the study show that: (1) the practice of buying and selling Instagram followers is illegal and this sale and purchase is a fraud. The reason for the invalidity of this practice is the non-fulfillment of the terms of the object of the contract, that is, the goods being traded must be fully owned by the seller, whereas in the buying and selling of followers, the seller is not the owner of the object of the contract and the shape of the object cannot be seen by both parties; (2) the jury of scholars differed on this type of ba'i, especially on the object of the contract which does not belong to the seller. The Syafii and Hambali schools say that it is invalid or unlawful even though they obtain permission from the representative or the owner, while the Hanafi and Maliki schools say that it is legal or permissible but is mauqūf (depending) on the willingness of the authorities (the owner or guardian). Jumhur scholars differ on the object of the contract that is not visible. The Shafi School says it is invalid or unlawful, while the Malik School and Hanafi School say it is permissible, but it is necessary to state the nature of the goods, and the buyer has the khiar to carry out or refuse the sale and purchase.